Expression of SoxE and SoxD genes in human gliomas. - Wegner, Michael; et al. (Neuropathology and Applied Neurobiology, 2007)
Members of group E and group D of the Sox gene family function as important transcriptional regulators of glial development in the central nervous system. Here, we have examined Sox gene expression in 60 human primary gliomas. Transcripts from each of the six group E and group D genes were expressed in gliomas of various types and malignancy grades, but with significant differences. SOX5, SOX9 and SOX10 were generally expressed at levels similar to or below those in adult brain tissue. In contrast, many oligodendrogliomas exhibited upregulation of SOX6, SOX8 and SOX13. Furthermore, loss of heterozygosity on chromosomal arms 1p and 19q was associated with significantly higher SOX8 mRNA levels. Low-grade astrocytomas, but not glioblastomas, also showed elevated SOX8 transcript levels. Taken together, the expression pattern of Sox genes in gliomas is heterogeneous and overall compatible with the less differentiated state of glioma cells as compared with their normal adult counterparts. Despite their restricted expression in astrocytes and oligodendrocytes during normal development, none of the Sox genes was selectively expressed in tumours of the oligodendroglial or astrocytic lineage. This is compatible with an origin of gliomas from neuroepithelial stem or precursor cells. © 2007 Blackwell Publishing Ltd.
UnivIS-Import:2015-03-09:Pub.2007.med.IB.LPCIPDBI.expres
Keywords: Astrocytoma; Oligodendroglioma; SoxD; SoxE; Sry-box